The Language Variations Used among Speakers of Sasak Lombok, West Nusa Tenggara - Sugianto, Sugianto; Hasby, Muhammad Asrul (JOLLT Journal of Languages and Language Teaching, 2023)
Sasak language is rich of language varieties, both in dialect (pronunciation) and vocabulary. It is a unique language which shows some influences from Java, Bali and Makasar as the neigbouring Islands. The research is aimed at revealing the language variations made by the â€œsasakâ€ speaker (an Austronesian language family) when they speak â€œsasakneseâ€. The research is qualitatively describe how the speakers of sasak stand the existence of their language by renewing, updating it through language variations to gain belonging sense among teens who were gradually used modern languages.Â For the sake of finding out accurate and valid data on sasaknese language variations used, some related literatures on relevant issues were deeply read and reviewed to provide the supporting data sources. The research data were collected and analyzed in qualitative ways. The model of data analysis were divided into three stages of data analysis, those stages are data reduction where the researcher selects and simplifies the big data into a more simple and readable one. And then display the data where the researcher fits the selected data into tables, matrixes or charts to support readerÂ data display. The last stage is conclusion drawing and verification where the researcher made some verifications data to draw a final conclusion of the research. After all, the reports the language variations exist in sasak language, a language that is spoken by native community who live in Lombok. This local language is now endangered for the ignorances.